The Effect of Islamic Corporate Governance, Sharia Compliance, Islamic Social Responsibility on the Profitability of Sharia Banks - Suci Romadhonia; Sri Lestari Kurniawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The purpose of this study was to analyze the effect of Islamic Corporate Governance, Sharia Compliance and Islamic Social Responsibility on the profitability of Commercial Bankings (BUS) in Indonesia. This study uses a quantitative approach with samples of 12 BUS in the 2017-2020 period. The model used as an analytical tool is multiple regression analysis. Data processing in this study using SPSS 16.0. The results of this study indicate that simultaneously the variables Islamic Corporate Governance, Sharia Compliance (IsIR, PSR and ZPR) and Islamic Social Responsibility have a significant effect on Profitability (ROA) of SUB in Indonesia, while partially Islamic Corporate Governance has a negative and significant effect on Profitability (ROA), Sharia Compliance as measured by PSR has a positive and significant effect on Profitability, Sharia Compliance as measured by IsIR and ZPR has no significant effect on Profitability, and Islamic Social Responsibility has no significant effect on Profitability.Tujuan penelitian ini adalah untuk menganalisis pengaruh Islamic Corporate Governance, SC dan Islamic Social Responsibility terhadap Profitabilitas (ROA) BUS di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan populasi seluruh BUS di Indonesia dalam periode 2017-2020. Teknik pengambilan sampel dengan metode purposive sampling. Sampel yang memenuhi kriteria sebanyak 12 BUS dari total 14 BUS di Indonesia. Model yang digunakan sebagai alat analisis adalah analisis regresi berganda. Pengolahan data dalam penelitian ini menggunakan alat bantu SPSS 16.0 Hasil penelitian ini menunjukkan bahwa secara bersama-sama variabel Islamic Corporate Governance, Sharia Compliance (IsIR, PSR dan ZPR) dan Islamic Social Responsibility bepengaruh signifikan terhadap Profitabilitas pada BUS di Indonesia, sedangkan secara parsial Islamic Corporate Governance bepengaruh negatif dan signifikan terhadap Profitabilitas (ROA), Sharia Compliance yang diukur dengan PSR berpengaruh positif dan signifikan terhadap Profitabilitas, Sharia Compliance yang diukur dengan IsIR dan ZPR tidak berpengaruh terhadap Profitabilitas dan Islamic Social Responsibility tidak berpengaruh terhadap Profitabilitas.